Extraordinary influence how great leaders bring out the best in others - Irwin, Tim 1949- (Wiley, 2018)
"The age-old question for every leaderhow do we bring out the best in those we lead? Anyone who has run a company, raised a family, lead an army, or coached a team struggles to find the key to help others excel and realize their potential. It is surprising how often we resort to criticism vs. an approach that actually results in a better worker and a better person. What if we could speak Words of Life that transform those under our influence and ignite fires of intrinsic motivation? What if those we lead found great purpose in what they do and worked at their jobs with all their heart? Isnt that what leaders, parents and teachers really want? Ultimately, dont we hope to foster intrinsic motivation so that the individuals we lead become better employees, better students or better athletes? Recent discoveries of brain science and the wisdom of top CEOs that Dr. Tim Irwin interviewed for this book give us the answers weve long sought. In most organizations, the methods used to provide feedback to employees such as performance appraisal or multi-rater feedback systems, in fact, accomplish the exact opposite of what we intend. We inadvertently speak Words of Death. Brain science tells us that these methods tend to engage a natural negativity bias that is hardwired in us all. Science in recent years discovered that affirmation sets in motion huge positive changes in the brain. It releases certain neuro chemicals associated with well-being and higher performance. Amazingly, criticism creates just the opposite neural reaction. The most primitive part of the brain goes into hyper defense mode, compromising our performance, torpedoing our motivation and limiting access to our higher-order strengths. How do we redirect employees who are out-of-line without engaging our natural negativity bias? Leaders must forever ban the term, Constructive Criticism. Brain science tells us that we can establish a connection between the employees work and his or her aspirations. This book calls for a new approach to align workers with an organizations mission, strategy and goals, called Alliance Feedback"--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Leadership; Personnel management; Personnel Management; Personnel; Direction; BUSINESS & ECONOMICS; Human Resources & Personnel Management; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Management